Understanding the Dichotomy of Science - Hidayat, Syamsul (Universitas Muhammadiyah Makassar, 2023)
The development of science in the world in the Middle Ages resulted in an understanding of the dichotomy of science. The dichotomy of science is a view that separates science in general and religious science. This article aims to provide an understanding of the dichotomy from the history and background of its emergence, the factors that led to the emergence of a dichotomous understanding of science, the resulting impact and the efforts made to integrate science. By detailing and discussing the intricacies of the dichotomy of science, it is hoped that it will be able to provide a comprehensive and inclusive understanding of the integration and interconnection between scientific knowledge and religious beliefs.Keywords: Dichotomy; Science, History of Science